De l’exposition à la décomposition prismatique : art de la mémoire et arts visuels dans Speak, Memory de Vladimir Nabokov - Laure de Nervaux-Gavoty (Sillages Critiques)
References to the visual arts – painting, drawing, photography, the cinema and the magic lantern – play a central role in Speak Memory, reflecting the tensions underlying the workings of memory in Nabokov’s autobiography. Framing and pictorial devices allow the narrator to highlight significant episodes and salvage them from the flow of time while allusions to photography invite the reader to analyze the complex dialectic of light and darkness, and awareness and oblivion at work in the emergence of memories. Nabokov’s prismatic and reflexive aesthetic, lastly, is at the heart of a process of decomposition and transmutation which blurs the boundaries of truth and fiction and tries to come to terms with loss by performing a literary form of grief work.